Ability Analysis Of Waste Milkfish (Chanos chanos) As Alternative Medium Of Nutrient Agar On Escherichia coli And Staphylococcus aureus Growth: Analisis Kemampuan Limbah Ikan Bandeng (Chanos chanos) Sebagai Media Alternatif Agar Nutrien Pada Pertumbuhan Escherichia coli Dan Staphylococcus aureus - Pestariati; Syamsul Arifin; Gufron, Gusti Naila Rachmawati (Universitas Muhammadiyah Sidoarjo, 2022)
Waste milkfish got a lot from the residual processed milkfish production of Sidoarjo. The intestines, liver, and kidneys of waste milkfish contain protein, carbohydrates, and fat. The abundant availabilities were usable as a bacterial growth medium, including Nutrient Agar. Nutrient Agar has a high price and is produced by many foreign companies that can trigger a hard availability in laboratories of domestic healthcare, especially in frontier, outermost, and underdeveloped areas. This research aims to analyze the ability of waste milkfish as an alternative medium for Nutrient Agar on the growth of Escherichia coli and Staphylococcus aureus. The ability has been observed by the characteristics and number of bacterial colonies. This research was held in the bacteriology laboratory of the Medical Laboratory Technology Department, Health Polytechnic of Surabaya health ministry. The research type was True-experimental with a post-test-only control group design. Based on the preliminary test results, the waste milkfish mass variations were found in 7 grams, 7.5 grams, 8 grams, 8.5 grams, and 9 grams. Bacteria have been inoculated by the spread plate method, bacterial colony growth has been calculated by the Total Plate Count method. The data were analyzed by the Kruskal-Wallis test with a Sig. value <0.05 that there were differences in the number of Escherichia coli and Staphylococcus aureus colonies in milkfish waste media with various mass. The results showed that the best ability of waste milkfish as an alternative medium for Nutrient Agar on bacterial growth was found in 9 grams mass variation. the average number of Escherichia coli colonies were 186 × 1013 CFU/mL and Staphylococcus aureus colonies were 188 × 1013 CFU/mL.